2021
DOI: 10.1002/eap.2249
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Dirichlet process community occupancy model to estimate community structure and species similarity

Abstract: Community occupancy models estimate species‐specific parameters while sharing information across species by treating parameters as sampled from a common distribution. When communities consist of discrete groups, shrinkage of estimates toward the community mean can mask differences among groups. Infinite‐mixture models using a Dirichlet process (DP) distribution, in which the number of latent groups is estimated from the data, have been proposed as a solution. In addition to community structure, these models es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…However, we found identifiability issues in some of our simulations due to label‐switching among clusters. (Similar issues were reported by Sollmann et al (2021) when using infinite mixtures for modelling the joint distribution of occupancy parameters, especially when variation among clusters was high). Thus, in this work, we have specified finite mixtures for the state process only because our primary goal is to identify species based on their rarity rather than their elusiveness.…”
Section: Methodssupporting
confidence: 77%
See 3 more Smart Citations
“…However, we found identifiability issues in some of our simulations due to label‐switching among clusters. (Similar issues were reported by Sollmann et al (2021) when using infinite mixtures for modelling the joint distribution of occupancy parameters, especially when variation among clusters was high). Thus, in this work, we have specified finite mixtures for the state process only because our primary goal is to identify species based on their rarity rather than their elusiveness.…”
Section: Methodssupporting
confidence: 77%
“…Unfortunately, selecting appropriate proposal densities is challenging and difficult to implement (Nasserinejad et al, 2017). Recently, Sollmann et al (2021) proposed a truncated stick‐breaking Dirichlet process to describe the community structure in terms of the estimated classes and the similarity in species responses to environmental conditions. However, Sollmann et al (2021) reported an overestimation of the number of classes and poor mixing due to label‐switching issues attributed to high dimensionality and variability among clusters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, additional information, such as population temporal trend data, taxonomy, conservation status, and habitat usage, are essential, all of which can be obtained from the International Union for Conservation of Nature (IUCN) [ 267 ]. Additional parameters to include in the model algorithm comprise metabolic rate, body temperature and body mass, and foraging characteristics (e.g., such as diet, foraging strata, and foraging time), which may be downloaded from databases BirdLife International and IUCN12 [ 267 , 268 , 269 ]. Global distribution data sets are also collected, which indicate the bearing of other factors, such as bioclimatic variables, mammalian and avian biodiversity, and anthropogenic variables, all of which are obtained from multiple sources [ 270 , 271 , 272 ].…”
Section: Potential Areas Of Future Research Endeavorsmentioning
confidence: 99%